Influence of a signal description model on the calculations of the efficiency indicators of optoelectronic systems - Strelkova, T.; Lytuyga, A.; Kalmykov, A.; Khoroshun, G.; Riazantsev, A.; Ryazantsev, O. (НПП ЧП "Технологический Центр", 2020)
The work is aimed at establishing the boundaries of the use of models for describing signals in optoelectronic systems in calculating efficiency. A description of the signal formation process is proposed, taking into account the corpuscular and wave properties when registering signals in a wide range of intensities. A description of the statistical features of the output signals depending on the energy properties of the signal and noise components is proposed. It is shown that when describing the output signals of optoelectronic systems that register signals with different properties, Poisson and Gaussian distributions are used. The invariance of Poisson flows determines the description of an additive mixture of signal and background flows using Poisson flow. The efficiency of optoelectronic systems is calculated by the signal-to-noise ratio criterion based on the corpuscular and wave description of signals. Efficiency calculations have shown the expedience of using this criterion, provided that the statistical properties of signal and background flows are stabilized. It is shown that under the condition of changes in the energy characteristics of signals, from the point of view of the wave and corpuscular models, the statistical characteristics of the signals have different descriptions. The analysis of theoretical methods of signal analysis in optoelectronic systems is carried out, which is aimed at an adequate characteristic of the system operation, depending on the conditions of its operation. Taking into account the method of describing the process of receiving and processing signals will take into account additional statistical characteristics of signals, for example, an increase of the variance of the output signal. The use of adaptive methods for describing signals will make it possible to increase the efficiency of systems when receiving strong signals in a difficult interference environment, as well as when receiving weak signals
Вплив моделі опису сигналів на розрахунки показників ефективності оптико-електронних систем
Keywords: optoelectronic system; statistical model; corpuscular theory; wave theory of light; detection